Development of [89Zr]Zr-hCD103.Fab01A and [68Ga]Ga-hCD103.Fab01A for PET imaging to noninvasively assess cancer reactive T cell infiltration: Fab-based CD103 immunoPET - Xiaoyu Fan; Marta A. Ważyńska; Arjan Kol; Noemi Perujo Holland; Bruna Fernandes; Sander M. J. van Duijnhoven; Annechien Plat; Hans van Eenennaam; Philip H. Elsinga; Hans W. Nijman; Marco de Bruyn (EJNMMI Research, 2023)
Abstract Background CD103 is an integrin specifically expressed on the surface of cancer-reactive T cells. The number of CD103+ T cells significantly increases during successful immunotherapy and might therefore be an attractive biomarker for noninvasive PET imaging of immunotherapy response. Since the long half-life of antibodies preclude repeat imaging of CD103+ T cell dynamics early in therapy, we therefore here explored PET imaging with CD103 Fab fragments radiolabeled with a longer (89Zr) and shorter-lived radionuclide (68Ga). Methods Antihuman CD103 Fab fragment Fab01A was radiolabeled with 89Zr or 68Ga, generating [89Zr]Zr-hCD103.Fab01A and [68Ga]Ga-hCD103.Fab01A, respectively. In vivo evaluation of these tracers was performed in male nude mice (BALB/cOlaHsd-Foxn1nu) with established CD103-expressing CHO (CHO.CD103) or CHO-wildtype (CHO.K1) xenografts, followed by serial PET imaging and ex vivo bio-distribution. Results [89Zr]Zr-hCD103.Fab01A showed high tracer uptake in CD103+ xenografts as early as 3 h post-injection. However, the background signal remained high in the 3- and 6-h scans. The background was relatively low at 24 h after injection with sufficient tumor uptake. [68Ga]Ga-hCD103.Fab01Ashowed acceptable uptake and signal-to-noise ratio in CD103+ xenografts after 3 h, which decreased at subsequent time points. Conclusion [89Zr]Zr-hCD103.Fab01A demonstrated a relatively low background and high xenograft uptake in scans as early as 6 h post-injection and could be explored for repeat imaging during immunotherapy in clinical trials. 18F or 64Cu could be explored as alternative to 68Ga in optimizing half-life and radiation burden of the tracer.